ASSESSMENT OF GREENHOUSE GAS EMISSIONS FROM DAIRY FARMING USING THE COOL FARM TOOL - Roxana VIDICAN; Anamaria MĂLINAȘ; Cristina MOLDOVAN; Anca PLEȘA; Mirela RANTA (Journal of Applied Life Sciences and Environment)
Climate change is one of the greatest challenges mankind has ever faced and could lead to potentially devastating global problems, with a need for urgent mitigation and adaptation. Agriculture, especially livestock farming, is a major driver of climate change through its contribution to the total emissions of greenhouse gases (GHGs). The dairy sector has been identified as an important source of GHG emissions, mainly via carbon dioxide (CO2), methane (CH4) and nitrous oxide (N2O). In this study, total CO2 equivalent (CO2e) emissions were assessed from a dairy farm (65 dairy cows) located in Romania using the Cool Farm Tool calculator (CFT). We specifically aimed to calculate: (1) the total CO2 equivalent (CO2e) and CO2e per kg FPCM (fat- and protein-corrected milk); (2) methane emissions from enteric fermentation; (3) GHGs resulting from feeding practices; (4) GHGs from manure management; and (5) a simulation of two different scenarios and their impact on GHG emissions. Our results showed annual GHG emissions of 553,170 kg CO2e, almost half of which were released through enteric fermentation. Lactating cows were the major contributor to total GHG emissions, while heifers released the lowest emissions. The two scenarios simulated in this study showed that both the changes made in dairy diet composition and livestock manure management could result in lower GHG emissions. These results confirm the importance and utility of the CFT for the quantification of GHG emissions in dairy farms and its important role as a decision support tool to guide the adoption of good agricultural practices.